Videogames in Education: Benefits and Harms - Núñez-Barriopedro, Estela; Sanz-Gomez, Yeray; Ravina-Ripoll, Rafael (Revista Electrónica Educare, 2020)
In education, a paradigm is shifting to a more innovative teaching-learning process. Specifically, this paradigm focuses on including video games in classrooms as a teaching resource intended to obtain a more entertaining, efficient, and pleasant quality education for students. The proposed research aims to analyze whether there are significant differences among users of video games on the benefits or harms they bring, especially in education, or there is a positive or negative general opinion, as other authors noted, on the influence of video games on users’ behavior. To analyze the viewpoints on video games, first, we do an exploratory study through the literature. Then, we do a correlational survey study where Cluster Analysis and Multiple Correspondence Analysis are used. In this study, we took 400 Spanish consumers aged between 11 and 64 years without discrimination, regardless of sex. Among the results obtained, we can emphasize the creation of several groups with significant differences in their points of view, in some cases, very positive and in others more conservative. These results lead to conclude that the users’ opinions about how video games can affect their self-growth are being more positive, opening doors for using video games in education and other sectors.